Chemical stability of water in the water supply network - preliminary research = Stabilość chemiczna wody w sieci wodociągowej - badania wstępne - Płuciennik-Koropczuk, Ewelina; Kumanowska, Patrycja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of research on changes in selected water parameters during distribution in the water supply network of the city of 22 thousand inhabitants. Water parameters were controlled at 8 points in the network, distant from Water Treatment Plant from 0.4 to 3.1 km. The location of control points was selected in order to assess the water quality depending on the pipe material and at unfavourable points - at the ends of the network.
Keywords: secondary contamination of water; water supply network; water quality; wtórne zanieczyszczenie wody; sieć wodociągowa; system dystrybucji wody; jakość wody